The application of in situ TEM on the grain boundary brittleness of precipitation-strengthened Ni-based superalloys: Recent progress and perspective - Zhou, Qian; Ding, Qingqing; Zhang, Yuefei; Wei, Xiao; Zhang, Ze; Bei, Hongbin (Frontiers in Metals and Alloys, 2022)
Due to their superior strength and oxidation resistance at high temperatures, precipitation-strengthened Ni-based superalloys are widely used in load-bearing hot components in energy generation systems, such as gas/steam engines in aircraft or power plants. However, brittleness originating from a grain boundary (GB) in a certain temperature range is one of the greatest deadlocks, which desperately restricts their thermal-mechanical processing capabilities and also industrial applications. Experimental and theoretical investigations of the origin of GB brittleness with aims to overcome it still attract many research efforts in the high-temperature material field. It is desirable to understand the GB embrittlement mechanism by dynamically investigating the entire GB cracking process in real time under stress/temperature combination, which might be hardly revealed by a traditional experiment on precipitation strength/theoretical technologies. Current advances in high-temperature mechanical testing systems, which can be operated in a transmission electron microscope (TEM), provide unique opportunities for in situ exploration of the mechanistic origins of GB brittleness of superalloys with the resolution up to an atomic scale. Here, we first briefly give an overview of the phenomenon and current understanding on GB brittleness, followed by introducing the state-of-art techniques in an in situ TEM/mechanical testing system (MTS). In the end, we will also discuss the potential application of the in situ TEM/MTS on GB brittleness and a perspective overlook.